Respuesta :

2x(x+4)-1(x+4)
2x^2+8x-x-4
2x^2+7x-4

Answer: [tex]2x^2+7x-4[/tex].

Step-by-step explanation:

To find : The product of [tex](2x-1)(x+4)[/tex]

Using distributive property : [tex]a(b+c)=ab+ac[/tex] , we have

[tex](2x-1)(x+4)\\\\= (2x-1)x+(2x-1)4[/tex]

Again , using distributive property : [tex](b+c)a=ba+ca[/tex] , we have

[tex](2x-1)x+(2x-1)4=2x\cdot x+(-1)x+2x\cdot 4+(-1)4\\\\=2x^2-x+8x-4\\\\= 2x^2+7x-4[/tex]

Hence, The product of [tex](2x-1)(x+4)[/tex] is [tex]2x^2+7x-4[/tex].